2022
DOI: 10.1111/1759-7714.14589
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of microwave ablation for lung cancer adjacent to the interlobar fissure

Abstract: Background This retrospective study aimed to assess the safety and efficacy of microwave ablation for lung tumors adjacent to the interlobar fissures. Methods From May 2020 to April 2021, 59 patients with 66 lung tumors (mean diameter, 16.9 ± 7.7 mm; range, 6–30 mm) adjacent to the interlobar fissures who underwent microwave ablation at our institution were identified and included in this study. Based on the relationship between the tumor and the interlobar fissure, tumors can be categorized into close to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Furthermore, in a study assessing the safety of MWA procedures adjacent to the interlobar fissure, the overall success rate for ablation was 95.5%, and the PFS rates at 3, 6, 9, and 12 months were 89.4%, 83.3%, 74.2%, and 63.6%, respectively [ 4 ]. Common complications observed included pneumothorax (34.8%), pleural effusion (24.2%), cavity formation (18.2%), and pulmonary infection (7.6%) [ 4 ]. Other complications of MWA include pulmonary hemorrhage, chest wall injury, pulmonary abscess, thermal injury to adjacent structures, and tumor recurrence [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study assessing the safety of MWA procedures adjacent to the interlobar fissure, the overall success rate for ablation was 95.5%, and the PFS rates at 3, 6, 9, and 12 months were 89.4%, 83.3%, 74.2%, and 63.6%, respectively [ 4 ]. Common complications observed included pneumothorax (34.8%), pleural effusion (24.2%), cavity formation (18.2%), and pulmonary infection (7.6%) [ 4 ]. Other complications of MWA include pulmonary hemorrhage, chest wall injury, pulmonary abscess, thermal injury to adjacent structures, and tumor recurrence [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other complications of MWA include pulmonary hemorrhage, chest wall injury, pulmonary abscess, thermal injury to adjacent structures, and tumor recurrence [ 1 ]. It was suggested that puncturing the antenna through the interlobar fissure might pose a potential risk for complications [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the above cohorts demonstrated an excellent safety profile of BMWA with a lower rate of pleuralbased complication than percutaneous ablation, although future prospective studies are needed to confirm this. Subpleural or lesions close to the pleura poses additional risks relating to pleuralbased complications [87]. Our experience has shown that in around 66.7% of BMWA cases the ablation zone reached the pleura, and yet, the rate of pneumothorax was only for subpleural lung nodules [89].…”
Section: The State-of-art Of Bronchoscopic Microwave Ablationmentioning
confidence: 95%
“…Lung tumors may be close to vital organs, demanding precise targeting to avoid harming healthy tissues [80] Implement Focused Antenna Design and Beamforming: Design antennas with focused radiation patterns and employ beamforming techniques to concentrate energy on the tumor while minimizing exposure to surrounding healthy tissues [80], [81].…”
Section: Minimizing Damage To Healthy Tissuesmentioning
confidence: 99%